The unlikely legalization of medical cannabis in Albania: a case study - Gentian Vyshka (Journal of Medical Ethics and History of Medicine, 2019)
Cannabis abuse has been an issue of major concern for the Albanian society in recent years, following the wide illegal planting of the species. Legal lacunas, weaknesses from the drug-controlling agencies, and the easiness of harvesting Cannabis sativa plants have contributed to the creation of a general negative opinion toward a potential use of its active principles for medical purposes. Professionals of the field and policymakers are largely focused on harm reduction activities, thus bypassing the option of legalizing cannabinoids for clinical conditions that might find relief in their use.The discussion of a case suffering from postherpetic neuralgia shows how this negative opinion is depriving Albanian patients from an otherwise helpful pharmacological option whose efficacy has been confirmed by an important bulk of research. Uncovering the roots of this misperception will help address the issue. Clinicians with expertise need to have their say in the debate, since for the majority of countries where medicinal cannabis is legalized, this was due to consumer-led initiatives. Ensuring patients’ freedom as implied within the principle of autonomy is also a sound ethical support of such legalization.